IMPLEMENTASI STRATEGI SEE THINK WONDER PADA PENGEMBANGAN MEDIA EDUKATIF UNTUK ANAK USIA 8-10 TAHUN DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS - Devanny Gumulya; Christina Renata Gultom (Universitas Trisakti, 2024)
Implementation of the See Think Wonder Strategy in the Development of learning kit for 8 – 10 years old Children to Enhance Critical Thinking Skills. This research aims to investigate the implementation of the See Think Wonder strategy in the development of learning kit for children, focusing on enhancing critical thinking skills through art appreciation activities. The See Think Wonder strategy is a thinking routine developed by Harvard with the goal of teaching children to engage in careful observation, wise interpretation, and stimulating curiosity to progress to the investigation stage. The research method employed is qualitative with a research through design approach, adopting the instructional model framework of ADDIE (analyze, design, develop, implement, and evaluate). The study involves the participation of children aged between 8 and 10 years. The findings of the research indicate that children show high interest and participation in developing critical thinking skills through art appreciation activities using the See Think Wonder strategy. Furthermore, it was discovered that children have a better understanding of the See stage, while they require more profound guidance in the think and wonder stages. The implications of this research can be used as a guide in the development of learning programs that focus on enhancing critical thinking skills in children, particularly through art appreciation activities using the See Think Wonder strategy in educational media.